Predictive factors for the effectiveness of novel androgen receptor axis‐targeted agents in patients with metastatic prostate cancer. (7th September 2022) - Koshiro, Nishimoto; Nakajima, Kenichi; Oyama, Masafumi; Kaneko, Go; Takahashi, Satoru; Matsuyama, Hideyasu; Shiina, Hiroaki; Ichikawa, Tomohiko; Horikoshi, Hiroyuki; Hashine, Katsuyoshi; Sugiyama, Yutaka; Miyao, Takeshi; et al.
Abstract : Objective: Novel androgen receptor axis‐targeted agents (ARATAs) have been developed for mCRPC and improved overall survival (OS). Here, we aimed to find predictors who will receive the greatest benefits from ARATAs. Methods: We previously performed a multicenter study to identify prognostic factors for metastatic hormone‐sensitive prostate cancer (mHSPC, n = 148) and mCRPC ( n = 99), and showed that the bone scan index (BSI) was one of the significant prognostic factors for 3‐year OS (PROSTAT‐BSI study). mHSPC progressed to mCRPC ( n = 101), for which 69 patients were treated with ( n = 39) or without ARATAs ( n = 30, prior to the approval of ARATAs). The 69 patients were divided into two groups according to patient factors, and these cohorts were further divided into two subgroups by usage of ARATAs. OS was compared between subgroups in each group. Results: The predictors were age (<71.4 years), serum levels of C‐reactive protein (≥0.16 ng/ml) and alkaline phosphatase (≥548 U/L), time to PSA progression after ADT (<8.9 months), the lowest PSA level (≥1 ng/ml) after ADT, and the rate of PSA decline 3 months after ADT (<0.987), whereas hemoglobin levels, PSA before ADT, Gleason scores, existence of visceral metastases, and BSI were not. Conclusions: The present study identified predictors for the effectiveness of ARATAs. The number of bone metastases (≒BSI), existence of visceral metastases, and Gleason scores, which were identified as high‐risk factors in the LATITUDE study and disease volume in CHAARTED criteria, did not appear to be useful for predicting effectiveness from ARATAs.